Pengembangan Ekonomi Kreatif dalam Pengelolaan Dodol Ibu Wiwin untuk Meningkatkan Pendapatan Masyarakat di Desa Caringin Kecamatan Caringin Berlandaskan Ekonomi Syariah - Jaenudin, Mupti; Ilyas, Amin (ALIF: Sharia Economics Journal, 2023)
The purpose of this study was to determine how the management of dodol products by Mrs. Wiwin, a micro-business owner in Caringin Village, Caringin district, can contribute to the growth of the creative economy based on Islamic economic principles. Sharia economics, which is based on Islamic principles, encourages justice, ethics, and sustainability in the economy. This object is interesting to study in the context of the development of the local creative economy. This study uses qualitative research methods that involve in-depth interviews with Ibu Wiwin and members of the local community, participatory observation, and analysis of documents related to Islamic economics. The results showed that dodol products made by Ibu Wiwin have properties that are in accordance with Sharia economic principles such as halal, justice, and sustainability. This study also found that management based on local wisdom and environmental concerns is the main focus in the production process of dodol. The income of the people of Caringin village has increased since Ibu Wiwin implemented the concept of sharia economics in the management of dodol. Community involvement in the production and marketing of dodol has increased local economic participation, which helps to reduce economic disparities. This study emphasizes how important it is to combine the concept of creative economy with the principles of Islamic economics to produce innovative solutions for the sake of local economic growth. This study shows that other micro-business actors can use this method to increase the income and welfare of the community in various places.